Influencing factors of glymphatic system during perioperative period - Dong, Rui; Liu, Wenjie; Han, Yuqiang; Wang, Zimo; Jiang, Linhao; Wang, Liwei; Gu, Xiaoping (Frontiers in Neuroscience, 2024)
The glymphatic system is a functional cerebrospinal fluid circulatory system that uses peri-arterial space for inflow of cerebrospinal fluid and peri-venous space for efflux of cerebrospinal fluid from brain parenchyma. This brain-wide fluid transport pathway facilitates the exchange between cerebrospinal fluid and interstitial fluid and clears metabolic waste from the metabolically active brain. Multiple lines of work show that the glymphatic system is crucial to normal brain functions, and the dysfunction of the glymphatic system is closely associated with various neurological disorders, including aging, neurodegeneration, and acute brain injury. Currently, it is common to explore the functional and molecular mechanisms of the glymphatic system based on animal models. The function of glymphatic system during perioperative period is affected by many factors such as physiological, pathological, anesthetic and operative methods. To provide a reference for the interpretation of the results of glymphatic system studies during perioperative period, this article comprehensively reviews the physiological and pathological factors that interfere with the function of the glymphatic system during perioperative period, investigates the effects of anesthetic drugs on glymphatic system function and the potential underlying mechanisms, describes operative methods that interfere with the function of the glymphatic system, and potential intervention strategies based on the glymphatic system. Future, these variables should be taken into account as critical covariates in the design of functional studies on the glymphatic system.